PNEUMATIZATION PATTERNS IN THE TEMPORAL COMPONENT OF THE TEMPOROMANDIBULAR JOINT - A CONE-BEAM COMPUTED TOMOGRAPHY ORIGINAL STUDY AND REVIEW - Cătălina Bichir; Mugurel Constantin Rusu; Mihai Săndulescu; Ruxandra Stănescu (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study This study aimed to establish the pneumatic patterns of the temporo-mandibular joint (TMJ) in cone-beam computed tomography (CBCT) and to review the specific literature as compared to the results. Material and methods A retrospective study of the archived CBCT files of 111 patients was performed (i.e.222 temporal bones). The TMJ temporal bone area was analyzed on planar cuts (axial; coronal and sagittal), and grading systems were established for each plane to indicate the degree of the pneumatic air tract extent. Results Twenty-nine different patterns of pneumatization were found. Fifty-five percent of the lot had no pneumatization at all in the TMJ area, while 20.3% presented air cells only in the posterior root of the zygomatic arch. Prevalence in the remaining patterns was less than 2% for each pattern. Conclusions Air cells in the temporal bone are unpredictable and impossible to locate without the help of high accuracy radiological investigations. Their presence may impact the function of the TMJ and are to be considered as risk factors for intraoperative and postoperative complications.